2020
DOI: 10.1002/hep4.1501
|View full text |Cite
|
Sign up to set email alerts
|

Differential Associations of Circulating MicroRNAs With Pathogenic Factors in NAFLD

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a heterogeneous disease driven by genetic and environmental factors. MicroRNAs (miRNAs) serve as pleiotropic post-transcriptional regulators of cellular pathways. Although several miRNAs have been associated with NAFLD and fibrosis, there are limited studies in humans examining their differential association with pathogenic factors or histological features of NAFLD. We examined the differential relationships of five of the best-described circulating microRNAs (miR-34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 48 publications
(56 reference statements)
2
26
1
Order By: Relevance
“…MiRNAs are deregulated in NAFLD and have been proposed as useful biomarkers for the diagnosis and stratification of disease severity of NAFLD and NASH 5 . We found 24 studies 2,6‐9,26‐43 that investigated the association of miRNAs with FLD (Table 2). Of these, 13 studies used blood samples, 6,26‐36 three studies used liver tissue 2,37,38 and eight studies used both blood and liver tissue samples 7‐9,39‐43 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MiRNAs are deregulated in NAFLD and have been proposed as useful biomarkers for the diagnosis and stratification of disease severity of NAFLD and NASH 5 . We found 24 studies 2,6‐9,26‐43 that investigated the association of miRNAs with FLD (Table 2). Of these, 13 studies used blood samples, 6,26‐36 three studies used liver tissue 2,37,38 and eight studies used both blood and liver tissue samples 7‐9,39‐43 .…”
Section: Resultsmentioning
confidence: 99%
“…We found 24 studies 2,6‐9,26‐43 that investigated the association of miRNAs with FLD (Table 2). Of these, 13 studies used blood samples, 6,26‐36 three studies used liver tissue 2,37,38 and eight studies used both blood and liver tissue samples 7‐9,39‐43 . In addition, the studies included population with Asian (n = 9), European (n = 7), North American (n = 6) and South American (n = 2) ancestries with mean age of 46.9 years old.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Ono et al (57) identified miR-222 as a negative regulator of insulin resistance via the down-regulation of insulin receptor substrate-1 in the liver. An upregulation of miR-200a is associated with non-alcoholic fatty liver disease (58)(59)(60) , and in vitro studies show an increase in miR-200a expression in hepatocytes exposed to NEFA and proinflammatory factors (61) . Similar to miR-222, miR-200a may have been up-regulated in HFS-WM dams due to stress and the positive correlation between female offspring liver TAG and miR-222 and miR-200a may be explained through these inflammatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In human NAFLD/NASH studies, increased free-circulating levels of miR-15b, miR-28, miR-122, miR-132, miR-181a, miR-191, miR-192, miR-199a-5p and miR-199a-3p have been observed whereas decreased levels of miR-29c and miR-99a have been reported [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], which are in line with our findings in the liver of the CCl 4 -treated rats. Our observed inverse correlation of decreased hepatic miR-122 level and increased serum miR-122 level is consistent with previous reports in animal and human studies [ 14 , 31 , 47 , 76 ].…”
Section: Discussionmentioning
confidence: 99%